2018
DOI: 10.3389/fpsyt.2018.00422
|View full text |Cite
|
Sign up to set email alerts
|

Human Endogenous Retroviral Envelope Protein Syncytin-1 and Inflammatory Abnormalities in Neuropsychological Diseases

Abstract: Human endogenous retroviruses (HERVs) comprise approximately 8% of the human genome. Recent studies have considered HERVs as potential pathogenic factors. The majority of HERV genes are mutated and not capable of encoding functional proteins; regardless, some HERV genes, such as HERV-W envelope (env) glycoprotein, are known to have intact open reading frames. The HERV-W element on 7q21.2, which encodes a protein referred to as Syncytin-1, participates in human placental morphogenesis and can activate a pro-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 99 publications
(110 reference statements)
1
60
0
1
Order By: Relevance
“…The HERV-H env was selected because it is entirely present on the chr2q24.3. However, it has been reported that HERV-H env fragments can be found on human chromosomes 1, 2, 3, 4, 5,6,7,9,10,11,12,14,15,16,17,18,19,20, X, and Y, and they all might be subjected to change in the expression. To avoid this limitation, the future project will be focused on more HERV-H insertions, designing a specific PCR for each insertion, so that it could be possible identifying which one might be involved in the colon cancer pathogenesis.…”
Section: A Possible Relationship Between Dysregulation Of Herv-relatedmentioning
confidence: 99%
See 1 more Smart Citation
“…The HERV-H env was selected because it is entirely present on the chr2q24.3. However, it has been reported that HERV-H env fragments can be found on human chromosomes 1, 2, 3, 4, 5,6,7,9,10,11,12,14,15,16,17,18,19,20, X, and Y, and they all might be subjected to change in the expression. To avoid this limitation, the future project will be focused on more HERV-H insertions, designing a specific PCR for each insertion, so that it could be possible identifying which one might be involved in the colon cancer pathogenesis.…”
Section: A Possible Relationship Between Dysregulation Of Herv-relatedmentioning
confidence: 99%
“…The aim of the present study was to assess the putative relationship between HERVs and colon cancer through a comparative analysis of HERV-H, -K (HML-2), and -P env and HERV-K (HML-2) pol transcription; HERV-K Pol and Env protein expression; and HERV-H, -K (HML-2), and -PLTR methylation levels in malignant tissues and negative surgical margins collected from patients with advanced-stage disease. Additionally, HERV-W was investigated, as control, because of its physiological role and pathological association with diseases different from tumors (20).…”
Section: Introductionmentioning
confidence: 99%
“…Syncytin‐1 is a protein activating the proinflammatory pathways and autoimmune cascades. Syncytin‐1 is related to the neuroinflammation as well as oligodendrocyte death and is highly expressed in astrocytes, glial cell, and microglia of MS lesions . Saffron has been shown to have a protective effect in autoimmune encephalomyelitis (EAE) mice via inhibition of leukocyte infiltration and oxidative stress suggesting Crocin could be of therapeutic potential in the management of MS.…”
Section: Msmentioning
confidence: 99%
“…For example, HERV-E and HERV-H belong to class I, whereas HERV-K belongs to class II. 1 Full-length HERVs comprise gag, pol, env and two gene regulatory sequences on both sides of the 5ʹ and 3ʹ ends, namely, a long terminal repeat (LTR) ( Figure 1). 2 HERVs often lost coding ability but exist permanently in the genome due to deletion, mutation and hypermethylation.…”
Section: Introductionmentioning
confidence: 99%